Successfully Metode Workover : Re-Entry Dan Re-Evaluate Sumur Vertikal X-1 Dengan Sidetrack Dan Drilling Horizontal Pada Lapisan Top Reservoir - Natasya Dwi Novanti; Eriska Eklezia Dwi Saputri; Ida Bagus Gede Hermawan Manuaba (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2024)
The existing well X-1 is an old vertical well that has been producing oil for many years.Water Oil Contact interval increases until it reaches the perforation depth interval as long as production oil from well is taken . This causes water coning problems to arise, causing the water cut value in this well to reach 30%. To overcome this problem, the X-1 well was closed and a workover operation was carried out with sidetrack to look for the sweet spot oil zone by evaluating the formation of the pilot hole well using a wireline log and wireline formation tester. After the sweet spot oil zone is found, horizontal drilling is carried out in the sweet spot oil zone to create the Maximize Reservoir Contact well. This workover operation was carried out in order to find zones that contain almost 100% oil, as well as reduce water production. Economic calculations were carried out to analyze the success of the pilot hole and MRC well sidetrack workover project. The research methods used to evaluate pilot hole well formations are qualitative and quantitative using the modification archie equation for carbonate reservoir on a wireline log and validated with a wireline formation tester, as well as the method for calculating the feasibility of a workover project using the Indonesian version of PSC cost recovery economics. The results obtained are that the sweet spot oil zone is at a depth of XYY7 ft with water saturation values ​​0.269635 on the wireline log and 0.000122 on the wireline formation tester and oil saturation values ​​respectively are 0.730365 and 0.999878. Based on economic analysis using the Indonesian version of the PSC cost recovery method, it can be concluded that this project is feasible to operate with positive NPV results of $2579.57 MUSD, IRR value of 142% and POT of 1.46 months. Key Words : formation evaluation, wireline log, wireline formation tester, pilot hole well, MRC Well, sweet spot oil zone, water coning, PSC cost recovery.